Research Trends in Knowledge Grid - Owoc, Mieczysław L. (Trendy badawcze w koncepcji wiedzy sieciowej, 2009)
Among new solutions in sharing knowledge – grid processing seems to be one of the most promising. In the grid computing concept we find many advantages essential for business as well as for scientific groups that use large scale of knowledge resources. The aim of this paper is an investigation of the research areas that are essential for the knowledge grid discipline.The paper is divided into four sections. In the first one an introduction to knowledge grid concepts is presented, in the next one a general model of KG is discussed. The third crucial part refers to the major research areas while the last one presents conclusions.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 55, s. 289-295
Keywords: Knowledge Grid; grid computing; research areas